A Brief Analysis of Raymond Carver's Short Stories from a Marxism Perspective (British Journal of Multidisciplinary and Advanced Studies, 2022)
Marxist materialism shows that social existence determines social consciousness, so the era Carver writes about is not an era fabricated out of thin air; it is the era of the era in which he lives, and Carver's characters are also the characters of the era in which they live. The various stories of misfortune, bad and despair they experience are the evidence of the Vietnam War, the feminist movement, sexual liberation, the Watergate scandal, and a series of events that happened in this era. Most of Carver's characters work in sales, service, and other low-paying jobs, and they are part of the multitude of the proletariat. Just like Carver's own experience, he realized in his labor that the bourgeoisie oppressed and exploited them, and that the bourgeoisie's proclamation of equality and freedom for all was only a rhetoric to cover up their ugliness, selfishness, and unpleasantness. With his keen observation, Carver captures the objection of human beings in this era and sees the contradictions and conflicts of capitalist society. This paper will adopt the text-reading strategy to explore the process of alienation of Carver's characters, the realism of content creation and its roots, as well as the humanitarian light shining in it.